The Effect of Grammar Mastery and Self-Esteem towards Students’ Speaking Skill - Delis Meta Tiana; Jimmi Jimmi; Rina Lestari (Scope : Journal of English Language Teaching, 2023)
The study’s goal is to discover and to investigate how students’ grammatical knowledge and sense of self-worth influence their capacity for effective oral expression empirically. The researchers adopted a quantitative strategy and used a survey to gather information. Seventy-three students were selected at random from the population of students at selected Private Vocational High Schools in East Jakarta. In order to verify the hypotheses, a multiple regression analysis was performed. The study yielded the following findings. Self-Esteem and grammatical competence go hand in hand when it comes to a student’s ability to communicate clearly. The fact shows that Sig. = 0.000 < 0.05 and Fo= 25.662. Students' fluency with grammar has a major bearing on how well they can express themselves verbally since Sig. = 0.000 < 0.05 and to= 3.788 demonstrate this to be the case. Students' confidence in their own abilities has a major bearing on how well they can express themselves. This is evidenced by the congruence between the values Sig. = 0.000 < 0.05 and to= 4.921.